Mutual interplay of Ca2+ and ROS signaling in plant immune response. (June 2019) - Marcec, Matthew J.; Gilroy, Simon; Poovaiah, B.W.; Tanaka, Kiwamu
Highlights: The lock and key mechanism created by second messenger and physical signal signatures is applicable to plant responses. Recent advances in ROS and Ca 2+ signaling in plant immunity. Potential mechanisms for the interplay between ROS and Ca 2+ signaling. Abstract: Second messengers are cellular chemicals that act as "language codes", allowing cells to pass outside information to the cell interior. The cells then respond through triggering downstream reactions, including transcriptional reprograming to affect appropriate adaptive responses. The spatiotemporal patterning of these stimuli-induced signal changes has been referred to as a "signature", which is detected, decoded, and transmitted to elicit these downstream cellular responses. Recent studies have suggested that dynamic changes in second messengers, such as calcium (Ca 2+ ), reactive oxygen species (ROS), and nitric oxide (NO), serve as signatures for both intracellular signaling and cell-to-cell communications. These second messenger signatures work in concert with physical signal signatures (such as electrical and hydraulic waves) to create a "lock and key" mechanism that triggers appropriate response to highly varied stresses. In plants, detailed information of how these signatures deploy their downstream signaling networks remains to be elucidated. Recent evidence suggests a mutual interplay between Ca 2+ and ROS signaling has important implications for fine-tuning cellular signaling networks in plant immunity. These two signaling mechanisms amplify each other and this interaction may be a critical element of their roles in information processing for plant defense responses.